Faktor yang berhubungan dengan Rujukan Pasien Peserta BPJS di Puskesmas Bangkala Kota Makassar Tahun 2023 - Magfirah Magfirah; A. Rizki Amelia Ap; Wardiah Hamzah (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
The health service referral system is the organization of health services that regulates the delegation of duties and responsibilities of health services reciprocally both vertically and horizontally. The purpose of this study was to determine the factors related to patient referral participants (BPJS) at the Bangkala Health Center, Makassar City in 2023. . This type of research is a quantitative observational study using a cross sectional approach. The population in this study is the BPJS participant community who visited the Bangkala Health Center in Makassar City in the last month of 2022 with a total of 956 participants. The samples in this study were 282 samples. The sampling technique is using probability sampling method with accidental sampling technique. The results showed that there was no relationship with knowledge (p=0.873). Meanwhile, the variables significantly related to BPJS patient referrals were the availability of medicines (p=0.000) and the availability of medical devices (p=0.000). The conclusion from this study is that there is a relationship between the availability of medicines, the availability of medical devices and BPJS referrals. While the knowledge variable is not related to BPJS patient referrals.